A Genre–based Study of Case Response Writing on an MBA Programme - Nathan, Philip Bernard (Journal of Academic Writing, 2016)
Case-based assignments represent a common form of assessment on academic business programmes (Easton 1982 and Mauffette-Leenders, Erskine and Leenders 1997), with students required to generate amongst other responses, business case reports, case critiques and case analyses (Nathan 2013). Only limited research is available to support academic writing tutors in understanding such case response texts with published studies focusing solely on business case reports (Freedman and Adam 1994, Forman and Rymer 1999a, 1999b and Nathan 2013). In order to aid writing tutors in supporting academic business students, this paper presents a small corpus study of 36 case response non-report texts (ca. 40000 words), generated on a UK MBA programme. These texts represent categories designated case critique, case advisory and case comparison texts, and were written in three business specialisms, Marketing, Human Resource Management, and Finance, respectively. Rhetorical analysis identified variable rhetorical structure dependent on text category, although orientation, analytical and conclusion components were present at high frequency in all text categories. Substantial variability in citation frequencies, modal verb, business lexis, and first person pronoun deployment was also identified between text categories. Awareness of both similarities and differences in case-based writing responses should serve as a useful aid in informing academic writing pedagogy.